2023
DOI: 10.3389/fcvm.2023.978918
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the causal effects of genetically predicted plasma proteome on heart failure

Abstract: BackgroundHeart Failure (HF) is the end-stage cardiovascular syndrome with poor prognosis. Proteomics holds great promise in the discovery of novel biomarkers and therapeutic targets for HF. The aim of this study is to investigate the causal effects of genetically predicted plasma proteome on HF using the Mendelian randomization (MR) approach.MethodsSummary-level data for the plasma proteome (3,301 healthy individuals) and HF (47,309 cases; 930,014 controls) were extracted from genome-wide association studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
(48 reference statements)
1
1
0
Order By: Relevance
“…Although previous two-sample MR studies based on GWAS of lipid traits or eQTL of PCSK9 have provided support for the association between PCSK9 and all-cause HF [ 24 26 ], our study found no evidence of the correlation between circulating PCSK9 and the risk of all-cause HF. This aligns with previously published proteome-wide MR studies [ 46 48 ]. Consistent with our findings, a clinical observational study that adjusted for confounding factors, including age, sex, and diabetes, also reported no association between PCSK9 and all-cause HF [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although previous two-sample MR studies based on GWAS of lipid traits or eQTL of PCSK9 have provided support for the association between PCSK9 and all-cause HF [ 24 26 ], our study found no evidence of the correlation between circulating PCSK9 and the risk of all-cause HF. This aligns with previously published proteome-wide MR studies [ 46 48 ]. Consistent with our findings, a clinical observational study that adjusted for confounding factors, including age, sex, and diabetes, also reported no association between PCSK9 and all-cause HF [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…Recently, several studies have focused on identifying therapeutic targets for HF through the proteome-wide MR approach [ 46 48 ]. However, these studies have primarily focused on all-cause HF.…”
Section: Discussionmentioning
confidence: 99%